Merging lithium carbenoid homologation and enzymatic reduction: A combinative approach to the HIV-protease inhibitor Nelfinavir. Issue 18 (3rd May 2018) - Castoldi, Laura; Ielo, Laura; Hoyos, Pilar; Hernáiz, María J.; De Luca, Laura; Alcántara, Andrés R.; Holzer, Wolfgang; Pace, Vittorio
Abstract: An effective stereocontrolled synthesis of the HIV protease inhibitor Nelfinavir is reported. Two transformations were identified crucial for achieving success: the formation of a densely functionalized α-chloroketone via the homologation of a Weinreb amide with chloromethyllithium (LiCH2 Cl), followed by its erythro selective reduction into the corresponding chiral chlorohydrin. A commercially available enzyme P2-C02 was particularly well suited for this purpose, affording the key alcohol (in an excellent 99% de ), which was then smoothly converted into the active biologically active agent. Graphical abstract: